A Novel Hybrid Excitation Magnetic Lead Screw and Its Transient Sub-Domain Analytical Model for Wave Energy Conversion - Zhu, Lixun; Ma, Chao; Li, Wei; Huang, Min; Wu, Weimin; Koh, Chang-Seop; Blaabjerg, Frede (IEEE transactions on energy conversion, 2024)
A magnetic lead screw (MLS), that not only has enough maximum thrust force but also has good controllable performance, is a perfect linear actuator that can convert low-speed linear motion into high-speed rotary motion and apply for wave energy conversion system. In this paper, an improved transient sub-domain analytical model (SDAM) is proposed to analyze the performance of a novel proposed hybrid excitation magnetic lead screw (HEMLS) for the WEC system. The proposed HEMLS not only can have enough maximum thrust through the PM is arranged on both sides of the rotor and mover, but also can be controllable through two-phase windings that carry opposite DC and placed in slots on the mover. The proposed SDAM gives the analytical expressions of trust and torque. The hybrid exciting source and slot effect can be considered in the proposed SDAM. The proposed SDAM is validated by the finite element analysis method under both load and no-load conditions. Finally, a laboratory prototype and the corresponding test platform are developed to verify the effectiveness of the proposed HEMLS and its SDAM.